Book Development Model “English for Public Speaking” Toward Islamic Boarding Students - Nurhidayah, Yayah; Rofii, Agus; Kustini, Titin (Papanda Publisher, 2024)
English Public Communication refers to the process of conveying information, ideas, or messages to an audience in English with the aim of creating understanding, persuasion, or influence. This research aims to develop English for Public Speaking teaching materials to improve the English public communication skills of students in Islamic boarding schools. This study was carried out by considering the specific context of Islamic boarding schools as an educational environment. The research method used iR&D or Research and Development. In its implementation, the development of teaching materials includes the stages of needs analysis, design, development, implementation and evaluation. A needs analysis is carried out to understand the level of students' English public communication skills, as well as identifying aspects that need to be improved. The design and development of teaching materials was carried out by utilizing the principles of English for Public Speaking and adapted to the characteristics of Islamic boarding schools. The effectiveness of the